Depression and cognition: new insights from the Lorenz curve and the Gini index - Rafael Pérez-Ocón (International Journal of Clinical and Health Psychology, 2007)
This ex post facto prospective study reports the use of statistical techniquesknown as the Lorenz curve and Gini index to analyze the content of depressive cognitionsas a function of attributional negative style (i.e., internal, global and stable causalattributions for failure or negative events, as proposed by the learned helplessnessmodel) and negative cognitive triad (i.e., a negative view of oneself, ones future andones world, according to Becks cognitive model of depression). These statisticaltechniques revealed that attributional style was poorly related with depression level,whereas the negative cognitive triad showed a close relationship and provided a moreaccurate description of the depressive cognitive pattern. We also document how theLorenz curve and Gini index can be used to assess the predictive capacity of differentinstruments or the strength of the relationship between different variables and psychologicaldisorders, and to evaluate different models proposed to explain these disorders. Thispioneering study reveals the potential usefulness in Psychology of these statisticaltechniques, mainly used in Economical sciences, for analyzing the validity of differentfactors and possible predictors of specific psychological disorders, or to enhance existinginstruments, as our present study with depression shows.